The derivative and marginal cost, revenue, and profit - Zahrádka, Jaromír (Univerzita Pardubice, 2007)
The article is focused to describe several examples of economical and business problems which are solved by using derivations. The examples are used in mathematical courses in the first year of study (the first term) at the Faculty of Economics and Administration.

The article is focused to describe several examples of economical and business problems which are solved by using derivations. The examples are used in mathematical courses in the first year of study (the first term) at the Faculty of Economics and Administration.
Keywords: matematika; ekonomie; derivace; obchod; mezní náklady; mezní výnosy; mezní zisky